Quick Response Crisis Communication Strategies Insights from Public Relations PT. KAI DAOP 2 Bandung's Train Accident Response - Cintia Cintia; Tantri Aditya Susanti; Grisha Amanda; Muhammad Nuruzzaman; Aghnia Dian Lestari (Jurnal Syntax Transformation, 2024)
A crisis that occurs in a company has the potential to damage the company's reputation. However, if the crisis can be handled properly, then the crisis will not harm the company. The purpose of this research is to find out the crisis communication steps and efforts made by the Public Relations of Daop 2 Bandung in dealing with the crisis situation caused by the train accident. Researchers use a descriptive analysis approach because it is considered capable of describing something clearly and each part can be studied one by one, so that the facts of a case can be revealed transparently. Data collection techniques in the form of interviews, in this study the data source consists of primary data and secondary data. Primary data was obtained from interviews with Mr. Ayep Hanapi as Public Relations Manager of PT KAI Daop 2 Bandung. The results showed that PT KAI Public Relations has made several efforts to maintain the company's image, namely: First, pre-crisis PT KAI applies the zero accident principle by increasing employee competence and discipline as well as maintaining facilities and infrastructure. Second, PT KAI's crisis team collaborates with stakeholders, provides solutions, is responsive in serving the media by preparing accurate data and fact information. Third, post-crisis to improve the image by providing compensation to employees and accident victims and conducting evaluations to improve train safety and security in the future.